'No Man׳s Land': An exploration of the traumatic experiences of student midwives in practice. Issue 9 (September 2015) - Davies, Sarah; Coldridge, Liz
Abstract Background the role of being 'with woman' during traumatic birth has been identified as having an emotional cost for midwives, but to date no research has explored traumatic experiences of student midwives. Aim to explore student midwives׳ perceptions of what was traumatic for them and how they were supported with such events. Design a qualitative descriptive approach, using semi structured interviews. Setting one university in the North West of England. Participants 11 student midwives recruited by poster campaign. Findings five main themes emerged from the analysis. Wearing your Blues depicted what participants described as the 'bleak' landscape of practice. No Man's Land was concerned with traumatic tensions in the student role. 'Get the Red Box! ' and The Aftermath concerned traumatic events in practice and the impact of these on students. Learning to cope related to the way students coped with such incidents, as well as other stresses in the role. Key conclusions the student midwife inhabits a vulnerable position in the 'No Man's Land' of hospital practice. Her1 strong identification with the woman renders her potentially more vulnerable in traumatic situations. The study revealed a paradigmatic clash between the manualised care of a busy obstetric unit and the individualised woman-led approach they were expecting. Implications for practice it seems important for the profession to recognise that distressing events are not always the obvious critical incidents in care, and that a culture of support and/or debriefing after adverse events may assist students to articulate their needs and develop resilience. Educators may need to appreciate that the student midwife role in an emergency may heighten her vulnerability. This study also highlighted the potential alienation of students when placed in the maelstrom of a busy obstetric unit. The Birthplace study (Brocklehurst et al., 2011), NHS England's Five Year Forward View (NHS England, 2014) and NICE (2014) all recommend increasing the numbers of out-of-hospital births: it seems likely that such a reorganisation of care would improve the experiences of mothers and those who care for them during birth. As part of a 'design for compassionate care' (Crawford et al., 2014) it is important to foster spaces, processes and resources which are compassionate to practitioners and students.